Methods in Translation History: summer school Translation in History – History in Translation (September 2018) - Bollaert, Charlotte (chronotopos – A Journal of Translation History, 2020)
A report on the 2018 edition of the Vienna univie: summer school "Translation in History - History in Translation". The summer school focused on "Methods in Translation History" and was attended by an international group of PhD students.